ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN PADA BISNIS TOTE BAG CABICIKS DESA CURUG, KABUPATEN BOGOR - Nida, Shohwatun; Hilwa, Wirda; Fitri, Atiyah (GREAT: Jurnal Manajemen dan Bisnis Islam, 2024)
This study aims to find out how effective marketing sales are in increasing sales at Cabiciks tote bag business and marketing strategies through STP (Segmenting, Targeting, Positioning) and marketing mixwhich are applied to Cabiciks tote bag business. This reseach method uses a qualitative descriptive method and Cabiciks tote bag business as the object of research. The types of data used are primary and secondary data, namely the method of observation, interviews and documentation and using the SWOT analysis method (Strength, Weakness, Opportunity, Threat) to determine strategies that have an effect on increasing sales. Next is the selection of strategies generated by the SWOT matrix obtained from the company’s position on the SWOT analysis diagram. Then the alternative strategies obtained from the results of the SWOT analysis are reprocessed using the QSPM (Quantitative Strategic planning Matrix) matrix to find out the main priority strategies of the various alternative strategies. The results from the QSPM matrix of 10 strategies, there is 1 highest strategy that is maintaining the quality of raw materials for fabrics to balance the market demand which is quite busy for Cabiciks products.